2017
DOI: 10.1002/cpt.930
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine in Neonatal Abstinence Syndrome

Abstract: Infants exposed in utero to opioids will demonstrate a withdrawal syndrome known as neonatal abstinence syndrome (NAS). Buprenorphine is a long‐acting opioid with therapeutic use in medication‐assisted treatment of opioid dependency in adults and adolescents. Emerging data from clinical trials and treatment cohorts demonstrate the efficacy and safety of sublingual buprenorphine for those infants with NAS who require pharmacologic treatment. Pharmacometric modeling will assist in defining the exposure–response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Increasing the share of hospitals with written protocols for initiating nonpharmacologic management could decrease the use of pharmacologic treatments to promote parental presence and provision of care as well as standardize and improve the quality of pharmacologic treatments (e.g., initiation, weaning, discontinuation) when necessary [16,18]. We found substantial variation and room for improvement in pharmacologic treatments; for example, we found that the most common first-line pharmacologic treatments for NAS are oral morphine and methadone, though studies from clinical trials and treatment settings show that buprenorphine may be superior to either of these [41], and research suggests that methadone treatment may be superior to morphine treatment [42]. As results become available from clinical trials comparing pharmacologic treatments for NAS, hospital guidelines and protocols should be updated to maximize treatment strategies that reduce pharmacologic exposure and length of hospital stays.…”
Section: Discussionmentioning
confidence: 81%
“…Increasing the share of hospitals with written protocols for initiating nonpharmacologic management could decrease the use of pharmacologic treatments to promote parental presence and provision of care as well as standardize and improve the quality of pharmacologic treatments (e.g., initiation, weaning, discontinuation) when necessary [16,18]. We found substantial variation and room for improvement in pharmacologic treatments; for example, we found that the most common first-line pharmacologic treatments for NAS are oral morphine and methadone, though studies from clinical trials and treatment settings show that buprenorphine may be superior to either of these [41], and research suggests that methadone treatment may be superior to morphine treatment [42]. As results become available from clinical trials comparing pharmacologic treatments for NAS, hospital guidelines and protocols should be updated to maximize treatment strategies that reduce pharmacologic exposure and length of hospital stays.…”
Section: Discussionmentioning
confidence: 81%
“…Buprenorphine is a partial agonist of μ-opioid receptors used in adults for treatment of pain and narcotic addiction. It is also a valuable treatment option for neonatal abstinence syndrome, a condition affecting newborns that were exposed to opioids in utero (84). Norbuprenorphine, the major active metabolite, is a substrate of P-gp, which limits its brain distribution and partly masks its potential to provoke CNS depression (85).…”
Section: Cns Pharmacodynamic Response As a Surrogate Marker Of Brain mentioning
confidence: 99%
“…Buprenorphine has been rarely linked to overdose in adults and children. However, children under 2-3 years do not respond well to buprenorphine overdosage showing CNS toxicity such as respiratory and CNS depression, altered mental status and miosis (84,(86)(87)(88). In theory, immature P-gp in children could allow higher brain exposure to norbuprenorphine (83,87).…”
Section: Cns Pharmacodynamic Response As a Surrogate Marker Of Brain mentioning
confidence: 99%
“…In the context of the burgeoning opioid crisis, neonatal abstinence syndrome has become a major problem for babies born to addicted mothers . Buprenorphine has demonstrated an efficacy advantage over standard opioid replacement therapy for the neonatal abstinence syndrome in both controlled clinical trials and treatment settings . Buprenorphine is safe in the neonatal abstinence syndrome, and sublingual dosing has been demonstrated to be feasible in the neonatal population .…”
mentioning
confidence: 99%
“…Indeed, the use of sublingual buprenorphine resulted in a reduction in the median duration of treatment, median length of stay, and requirement for adjunctive therapies compared to oral morphine . It is noteworthy that the total number of treated patients in these cohorts is modest, although the consistency in effect size in different populations provides external validity to the findings . However, these types of studies, in which cohorts of patients available to individual investigators are modest, can be remarkably accelerated in the future by building public–private partnerships across heterologous platforms to share data, patients, and approaches through digital technologies …”
mentioning
confidence: 99%